Balanced Literacy Learning Model to Enhance Creative Thinking and Problem Solving in Elementary School Mathematics Word Problems - Meli Gusmawati; Deddy Sofyan S; Dadang Jaenudin (Universitas Suryakancana, 2026)
Persistent challenges in students' creative thinking and problem-solving capacities in mathematics — particularly in word problem contexts — call for innovative instructional models that bridge language comprehension and quantitative reasoning. This study aimed to examine the effectiveness of the Balanced Literacy learning model in enhancing creative thinking and problem-solving abilities among Phase C elementary school students in mathematics word problems. This study employed a quasi-experimental method using a non-equivalent control group design with pretest-posttest measurements. A total of 50 Grade V students from MI Assaidiyyah Cipanas, Cianjur Regency, were selected through purposive sampling and divided into an experimental class (n = 25) receiving Balanced Literacy instruction and a control class (n = 25) receiving conventional teaching. Data were collected through validated creative thinking tests, Likert-scale problem-solving questionnaires, and structured observation sheets, then analyzed using descriptive statistics and independent-samples t-tests via IBM SPSS Statistics 25. The results of this study indicate that the Balanced Literacy model significantly enhanced students' creative thinking (posttest mean: experimental 88.0 vs. control 80.8; N-Gain: 0.62 vs. 0.47) and problem-solving abilities (posttest mean: 95.48 vs. 93.04), with statistically significant inter-group differences (sig. < 0.05) for both outcomes. Observation data confirmed 100% implementation fidelity. The Balanced Literacy model, which integrates reading, writing, speaking, and listening within mathematical contexts, is recommended as an effective evidence-based approach for developing higher-order thinking in elementary mathematics. Keywords: Balanced Literacy; creative thinking; elementary school; problem solving; word problems